WHAT ARE COMPLEXONS? APPLICATION OF COMPLEXONES IN MEDICINE (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article discusses complexons, the composition and role of complexons in medicine. Studying the processes of interaction of metals with ligands, which are features of the properties of complexones, is the key to the search for new drugs. Complexones are an important antidote for heavy metal poisoning.